مهارة الكلام وطريقة تعليمها - Mabrurrosi, Mabrurrosi; Rohman, Fadlur; Hasbullah, M. (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
Education is a continuous process in all types and classes of learning. They are all related to the united learning method. And needs in learning goals, which are important in every aspect. Because the matter has no goals, it does not make sense, but a waste of time and energy. The direction of the process is clear with objectives. And the method and means as well as others that are appropriate in learning in order to quickly obtain goals. Speech is the means of human expression of thoughts and immobility, through the speech apparatus, to deliver them from sender to recipient in a society. The researcher used the descriptive approach in this research to reach the types of speaking skill and the method of teaching it.